MULTI-ELECTRODE RESISTIVITY SURVEY FOR GROUNDWATER EXPLORATION IN THE HARARE GREENSTONE BELT, ZIMBABWE - Owen R.J.; Gwavava O.; Gwaze P. (My University, 2006)
A multi-electrode resistivity survey, carried out over metasedimentary strata and metavolcanics in the Harare greenstone belt in northeastern Zimbabwe as part of a groundwater resources investigation, illustrates the ability of this technique to produce high-resolution images of the subsurface, which are useful for groundwater resources assessment. The resistivity results provide a clear view of the thickness of the weathered regolith and of the distribution of the various lithological units. Using a combination of apparent formation resistivity and inferred depth of weathering, it is possible to characterize the various lithologies on the geophysical profiles. These assigned lithologies show excellent correlation with the mapped geology, and the main lithologies, metabasalt, meta-arenite, granodiorite and banded iron formation can be clearly identified. The banded iron formation is characterized by low resistivity values, while a combination of the depth of weathering and resistivity values are used to distinguish between the meta-arenite on one hand and the metabasalt and granodiorite on the other. The multi-electrode method is successful in identifying potentially favourable zones for obtaining groundwater, such as areas with a maximum depth of weathered regolith, zones of fracturing and faulting, and high porosity and permeability zones associated with lithological contacts.
Keywords: ZIMBABWE; GROUNDWATER SURVEYING; MULTI-ELECTRODE RESISTIVITY; CRYSTALLINE BASEMENT AQUIFERS; DRILLING SITE SELECTION